Strengthening Teachers’ Digital Literacy Strategies in Islamic Religious and Character Education - Apriyani, Wilda; Sesmiarni, Zulfani (El-Rusyd, 2026)
The development of digital technology has brought significant changes to the world of education, including in Islamic Religious Education and Character Education. Integrating digital literacy into learning is a necessity to improve the quality of the learning process, expand access to learning resources, and foster students' critical thinking skills. However, the implementation of digital literacy in Islamic Religious Education learning still faces various challenges, both from student factors, educators, and learning support facilities. This study aims to analyze teachers' digital literacy development strategies in Islamic Religious Education and Character Education learning in high schools and identify various obstacles faced in its implementation. This study uses a qualitative approach with a case study research type. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, while data validity was tested using source triangulation. The results show that Islamic Religious Education teachers have developed digital literacy through the use of various digital media and platforms, such as PowerPoint, learning videos, Google Forms, Kahoot, and digital puzzles in learning and evaluation activities. The use of digital media has been proven to increase student motivation to learn, active participation, and understanding of learning materials. However, the implementation of digital literacy still faces several obstacles, including limited internet access, uneven distribution of school Wi-Fi networks, limited devices and internet quotas among students, and differences in students' digital interests and abilities. This study recommends the need to improve technological facilities and infrastructure, strengthen the digital competencies of teachers and students, and support school policies to realize more effective, innovative, and adaptive Islamic Religious Education learning to adapt to digital technology developments.